Pengaruh Media Audio Visual terhadap Hasil Belajar Siswa Kelas IV pada Pembelajaran Subtema Hewan dan Tumbuhan di Lingkungan Rumahku di SD Negeri 091496 Tanah Jawa - Fransisca Lestari Manalu; Lisbet. N Sihombing; Hetdy Sitio (Departement of Mathematics Education, 2023)
The purpose of this study was to find out whether the audio-visual learning media had an effect on the learning outcomes of fourth grade students in the animal and plant sub-theme learning in my home environment at SD Negeri 091496 Tanah Jawa or not. There are 2 hypotheses in this study, namely, (1) there is an effect of the use of visual media on the learning outcomes of class IV students of SD Negeri 091496 Tanah Jawa (H) and (2) there is no effect of using visual media on learning outcomes of class IV students of SD Negeri 091496 Tanah Java (Ho). This research method is an experimental method with the type of Pre-Experimental Design research using the